I-Series: Microsoft Office Access 2003 Introductory (I-series) - Wells Merrill (McGraw-Hill, 2004)
Stephen Haag is the Associate Dean of Graduate Programs and Director of the MBA program in the Daniels College of Business at the University of Denver. Prior to being Associate Dean, Stephen served as Chair of the Department of Information Technology and Electronic Commerce in the Daniels College of Business at the University of Denver. Stephen holds a B.B.A. and M.B.A. from West Texas State University and a Ph.D. from the University of Texas at Arlington. Stephen has been teaching in the classroom since 1982 and publishing books since 1984.